WeShareIt Game: Strategic Foresight for Climate-change Induced Disaster Risk Reduction. (2016) - Onencan, Abby; Van de Walle, Bartel; Enserink, Bert; Chelang'a, James; Kulei, Felix
Abstract: Nile Basin policy makers, at all levels, are constantly making quick decisions to address emergencies. The decisions are made in the context of a complex, uncertain, ever-changing and highly volatile basin. However, for these decisions to take into account future uncertainties, like climate-change induced disasters, policy makers need to enhance their capacity in strategic foresight. Strategic foresight helps them make more robust decisions that take into account deep uncertainties and thus buffer the basin from future natural disasters. The authors explore the contribution of serious gaming in enhancing the Nile Basin policy makers' capacity on strategic foresight. They present the findings from the application of a game-based, experimental study of a serious game known as WeShareIt. WeShareIt was played in Nairobi on 22 October 2015 by 11 participants from the Kenyan Ministry of Water and Irrigation and Moi University Centre for Public Sector Reforms. Data on the added value and contribution of the game to increased strategic foresight and disaster risk reduction were collected using pre-game, in-game and post-game questionnaires, together with a debriefing session and observations. The analysis shows that strategic foresight is an important element for effective disaster risk reduction. Observations in the game-based intervention provided evidence that the participants engaged in short term quick decision making and were not prepared for life-threatening natural disasters. The results of the experiment support the conclusion that serious gaming may be an effective and promising method for enhancing the capacity of policy makers on strategic foresight so as to prepare them for future climate induced natural disasters.